The Effect of Price Perception, Service Quality and E-WOM on Customer Satisfaction Through Purchasing Decisions of Rail Express Madiun - Dian Citaningtyas Ari Kadi; Hari Purwanto; Sutarni Ningtyas (Cita Konsultindo Research Center, 2022)
This study aims to analyze the effect of Price Perception, Service Quality and E-WOM on Customer Satisfaction through the Purchase Decision of Rail Express Madiun. This type of research is quantitative research. The number of samples used is 385 respondents. The sampling technique used is non-probability sampling, with the accidental sampling method. Data retrieval using a questionnaire with the distribution via google form. Tests were carried out through SPSS 20 software using validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, coefficient of determination test (R2), hypothesis test (t test) and path analysis.